ANALISIS KEMAMPUAN PENGGUNAAN KATA PENGHUBUNG DALAM KARANGAN NARASI SISWA KELAS III SD NEGERI 222 TAGGENTUNG KABUPATEN SINJAI - Musdalifa; Abd. Rahman Rahim; Anzar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The main problem in this study is how students' ability to use conjunctions in narrative compositions for grade III students of SD Negeri 222 Taggentung, Sinjai Regency. This study aims to determine students' ability to use conjunctions in narrative compositions for grade III students of SD Negeri 222 Taggentung, Sinjai Regency. This type of research is descriptive qualitative. The research procedure includes the stages of planning, implementation and research. The data from this study are in the form of narrative compositions obtained through tests, the data source in this study is 9 grade III students of SD Negeri 222 Taggentung. Based on the results of the study on students' ability to apply conjunctions in narrative compositions, the average pre-test score was 58.33 and the post-test was 66.11. Based on the assessment category, both scores are included in the sufficient category. However, the increase in scores reflects positive developments in narrative writing skills, especially in the use of conjunctions appropriately to create coherence between sentences. Students begin to be able to choose and use various types of conjunctions, such as time connectors, cause-effect, and additions, so that the sentence structure in their compositions becomes more coherent and logical. Thus, the ability to use conjunctions in narrative compositions of grade 3 elementary school students is classified as sufficient, but shows an increase after learning